2020
DOI: 10.1002/jcsm.12567
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcopenia: epidemiology, diagnosis, and treatment—facts and numbers

Abstract: Background Osteosarcopenia, the presence of osteopenia/osteoporosis and sarcopenia, is an emerging geriatric giant, which poses a serious global health burden. Methods and results The prevalence of osteosarcopenia ranges in community‐dwelling older adults [5–37% (≥65 years)] with the highest rates observed in those with fractures (low‐trauma fracture: ~46%; hip fracture: 17.1–96.3%). Among 2353 community‐dwelling adults, risk factors associated with osteosarcopenia include older age [men: 14.3% (60–64 years) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
264
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(282 citation statements)
references
References 54 publications
(146 reference statements)
4
264
0
14
Order By: Relevance
“…Osteoporosis and sarcopenia are both associated with aging, contributing to an increased risk of fracture (1,2). Sarcopenia refers to reductions in muscle performance with the loss of skeletal muscle mass, while osteoporosis is characterized by deficits in both trabecular and cortical bone.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis and sarcopenia are both associated with aging, contributing to an increased risk of fracture (1,2). Sarcopenia refers to reductions in muscle performance with the loss of skeletal muscle mass, while osteoporosis is characterized by deficits in both trabecular and cortical bone.…”
Section: Introductionmentioning
confidence: 99%
“…28 The concept of "osteosarcopenia" describes a subset of older persons affected by a combination of low bone density (osteopenia/osteoporosis) and low muscle mass, strength, and/or functional capacity (sarcopenia). [29][30][31] To manage this pathological condition, it is mandatory to diagnose it through adequate assessment of muscle function, particularly measuring gait speed. 31 Moreover, Bhasin et al 32 have recently shown that low gait speed might independently predict falls in community-dwelling older adults.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] To manage this pathological condition, it is mandatory to diagnose it through adequate assessment of muscle function, particularly measuring gait speed. 31 Moreover, Bhasin et al 32 have recently shown that low gait speed might independently predict falls in community-dwelling older adults. Our study also confirms the role of this outcome measure as a quick, safe, and highly reliable test for physical performance.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of WHODAS, Kaigo-Yobo, and GDSSF values among the four groups of study subjects occurred after adjustment for gender, age, marital status, economic level, smoking status, hypertension, diabetes, hemoglobin, uric acid, albumin, r-GTP, creatinine, and cholesterol. [22][23][24] Adjusted means and their 95% con dence intervals (CIs) were estimated by general linear model (GLM) and the post-hoc test is based on Turkey method. The SAS Version 9.4 program (SAS Institute Inc., Cary, NC) was used as the analysis tool, and the signi cance level was set to 0.05.…”
Section: Discussionmentioning
confidence: 99%